2019
DOI: 10.1080/09712119.2019.1662424
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and expression analysis of the CCR9 gene from cobia (Rachycentron canadum) following bacterial and poly I:C challenge

Abstract: Chemokine receptors play an important role in coordination of cell trafficking in many biological processes. In this study, a CC chemokine receptor 9 of cobia Rachycentron canadum (RcCCR9) was identified. Analysis of the ORF (1119 bp) of RcCCR9 revealed a predicted protein of 41.87 kDa with typical seven transmembrane domain architecture. RcCCR9 shared several conserved structural features with homologs from mammals and other fish, and had a consistent relationship with phylogenetic trees and sequence identiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Treg cells play central roles in maintaining intestinal homeostasis by restraining inappropriate immune responses in the gastrointestinal tract under healthy and pathological conditions (Campbell, 2015 ). The CCR9/CCL25‐chemokine axis controls Treg homing to the small intestine (Perrigoue et al , 2014 ), and CCR9–CCL25 pairing maintains sequence conservation and functional conservation in vertebrates (Devries et al , 2006 ; Galindo‐Villegas et al , 2013 ; Su et al , 2019 ), which is also consistent with the conservation of the small intestine in vertebrates (Devries et al , 2006 ; Bird & Tafalla, 2015 ). Notably, the gastrointestinal tracts of zebrafish and medaka express colon‐specific genes (Wang et al , 2010 ; Aghaallaei et al , 2016 ).…”
Section: Discussionmentioning
confidence: 61%
“…Treg cells play central roles in maintaining intestinal homeostasis by restraining inappropriate immune responses in the gastrointestinal tract under healthy and pathological conditions (Campbell, 2015 ). The CCR9/CCL25‐chemokine axis controls Treg homing to the small intestine (Perrigoue et al , 2014 ), and CCR9–CCL25 pairing maintains sequence conservation and functional conservation in vertebrates (Devries et al , 2006 ; Galindo‐Villegas et al , 2013 ; Su et al , 2019 ), which is also consistent with the conservation of the small intestine in vertebrates (Devries et al , 2006 ; Bird & Tafalla, 2015 ). Notably, the gastrointestinal tracts of zebrafish and medaka express colon‐specific genes (Wang et al , 2010 ; Aghaallaei et al , 2016 ).…”
Section: Discussionmentioning
confidence: 61%
“…Chemerin 1 is regulated by several cytokines and pathogen-associated molecular patterns (PAMPs), and its activation leads to up-regulation of the phosphatidylinositol 3-kinase/Akt signaling pathway and down-regulation of NF-κB [9] , [10] . Previous studies demonstrated that expression levels of some pro-inflammatory cytokines, e.g., IL-1β, IL-8, TNF-α , and chemokine CC ( CCR3 ) [36] , [37] , and chemokine receptor, CCR9 [38] , [39] , were up-regulated in immune organs of cobia following bacterial or poly I: C challenge. V. harveyi is a gram-negative, rod-shaped, facultatively anaerobic, and non-spore forming bacterial species, which can infect cobia and other fish species [34] , and poly I: C is a synthetic double-stranded RNA (dsRNA), which can mimic the viral infection [35] .…”
Section: Resultsmentioning
confidence: 99%